(untitled) (Research, Society and Development, 2021)
Concrete is a material highly used in civil construction, has high compressive strength, however when pulled it tends to crack and break. With the occurrence of these cracks and possible rupture, there is a fear that the structure will no longer meet its performance criteria or that its useful life will be reduced. Based on this problem, studies on bioconcrete have been developed, concrete capable of performing self-repair from the addition of gram-positive bacteria and their food medium in their preparation through the process of biomineralization. When in contact with water, this bacterium feeds and precipitates a layer of calcium carbonate, thus filling its cracks. Therefore, bioconcrete presents itself as a new alternative in the area of ​​civil construction. The objective of the research was to analyze a new way of repairing cracks by means of bacteria extracted from the soil. The methodology was divided into the stages of preparing the bacteria, preparing the concrete, preparing the cracks, preparing the food medium and treating these cracks. The results were analyzed qualitatively. Although the cracks have not been completely filled, significant results were obtained, in which test A stood out, as it visually had its cracks more filled than in test B. However, the time used in the methodology may not have been sufficient for the complete repair of these cracks.